Influence of School Culture, Headmaster Supervision and Interpersonal Communication Towards Teacher’s Social Behavior - Istiqomah, Devi Nurul; Ekosiswoyo, Rasdi; Eko Pramono, Suwito (Educational Management, 2019)
Exemplary teacher can be seen on how a teacher behaving in the school environment. School is an educational organization which has certain activities and rules. Those activities and rules will influence school staff behavior, including teachers’ social behavior. The aim for this research is to analyze the influence of school environmental effect: school culture and headmaster supervision on teachers’ social behavior through interpersonal communication. This research is a qualitative research with ex post facto design. The population of this research is vocational school teachers in Gajah Mungkur regency. Proportional stratified random sampling technique is used to take the sample of the research. The researcher uses questionnaire as the method of data collection. The researcher gives the questionnaire to respondent through validity and reliability test. The researcher also conducts path analysis consisting of two structural equations. The result of the research shows that school culture and headmaster supervision has a direct influence on the interpersonal communication at 48.5% and 42.7%, school culture, headmaster supervision and interpersonal communication skill has an indirect effect on teacher social behavior through interpersonal skill at -2.4% and -2.1%. Teacher social behavior tends to be influenced by school culture than headmaster supervision. Meanwhile, interpersonal communication skill is not an intervening variable that influence others variable relation. The number of factors that give influence on teacher social behavior other than research variables, the researcher suggests that the stakeholder (teacher, headmaster and school) should uphold character value implementation in every school activity.